Non-linear glacier response to calving events, Jakobshavn Isbræ, Greenland - Cassoto, Ryan; Fahnestock, Mark; Amundson, Jason M.; Truffer, Martin; Boettcher, Margaret S.; De La Pena, Santiago; Howat, Ian (International Glaciological Society, 2018)
Jakobshavn Isbræ, a tidewater glacier that produces some of Greenland’s largest icebergs and highest speeds, reached record-high flow rates in 2012 (Joughin and others, 2014). We use terrestrial radar interferometric observations from August 2012 to characterize the events that led to record-high flow. Jakobshavn Isbræ, a tidewater glacier that produces some of Greenland’s largest icebergs and highest speeds, reached record-high flow rates in 2012 (Joughin and others, 2014). We use terrestrial radar interferometric observations from August 2012 to characterize the events that led to record-high flow. We find that the highest speeds occurred in response to a small calving retreat, while several larger calving events produced negligible changes in glacier speed. This non-linear response to calving events suggests the terminus was close to flotation and therefore highly sensitive to terminus position. Our observations indicate that a glacier’s response to calving is a consequence of two competing feedbacks: (1) an increase in strain rates that leads to dynamic thinning and faster flow, thereby promoting desta- bilization, and (2) an increase in flow rates that advects thick ice toward the terminus and promotes restabilization. The competition between these feedbacks depends on temporal and spatial variations in the glacier’s proximity to flotation. This study highlights the importance of dynamic thinning and advective processes on tidewater glacier stability, and further suggests the latter may be limiting the current retreat due to the thick ice that occupies Jakobshavn Isbræ’s retrograde bed. We are grateful to many people and organizations that sup- ported this project. TRIs were purchased with funds from the Gordon and Betty Moore Foundation (GBMF2627). Field work was completed through NASA (NNX08AN74G). Cassotto was supported by the New Hampshire Space Grant Consortium (NNX10AL97H) and later by a NASA Earth and Space Science Fellowship Program (NNX14AL29H). We thank CH2 M HILL Polar Services and Air ...